Optimization of Vaname Shrimp Growth (Litopenaeus vannamei) in Feeding with The Addition of Moringa Leaf Extract (Moringa oleifera Lam) - Naban, Sulthon Hamid Faros; Lumbessy, Salnida Yuniarti; Rahmadani, Thoy Batun Citra (Jurnal Biologi Tropis, 2024)
The addition of moringa leaf extract is one way to increase the production of vaname vaname shrimp farming. Moringa leaves are considered as feed supplements because they contain active compounds that are beneficial for shrimp growth. This study aims to analyze the growth of shrimp vaname on feeding supplemented with moringa leaf extract. The method used in this study is an experimental method using a complete randomized design (RAL) with 4 treatments and 3 repetitions.  Shrimp used is the size of PL 25 and maintained for 50 days parameters measured include absolute weight, absolute length, SGR, molting frequency, survival rate (SR) and water quality parameters. The Data obtained were analyzed by statistical ANOVA test and then tested by DUNCAN test, as well as descriptive water quality parameters in anasis. The results showed that phytochemical compounds identified in moringa leaf extract are flavonoids, alkaloids, saponins, tannins, and phenolics. The addition of moringa leaf extract with different extraction time in commercial feed affects the growth, molting frequency and survival rate of vaname shrimp, but does not affect the absolute length of vaname shrimp. Moringa leaf extract with 60 Minutes extraction time is the best treatment with antioxidant content of 66.78% and vitamin C 133.76 mg / 100g so that it can increase the absolute weight of vanname shrimp by 2.4 g, specific growth rate of 0.052% / day, molting frequency of 2.0 times / head and survival rate of 67%.